Penguatan Daya Saing Produk Olahan Dodol Rumput Laut melalui Pelatihan Pemotretan Produk KWT Rasa Saling Sayang - Zuhdiyah Matienatul Iemaaniah; Yy Wima Riyayanatasha; Riezka Zuhriyatika Rasyda; Nuzla Af’idatur Robbaniyyah; Setyaning Pawestri; Lulu’ Ayu Faezatiy (FKIP Universitas Mataram, 2026)
Kuta Village is a coastal area with abundant seaweed potential, which has been utilized by the community through various processed products. The Rasa Saling Sayang Women Farmers Group (KWT) cultivates seaweed, most of which is sold fresh at relatively low prices. Processing seaweed into products such as dodol, jelly, and flour can increase added value and has the potential to strengthen the family economy of group members. However, limited skills in product photography result in less attractive product visuals, thus impacting low competitiveness in the digital market and social media. This community service activity aims to improve the skills of KWT Rasa Saling Sayang members in producing aesthetically pleasing seaweed product photos that meet digital marketing needs. The activity method is implemented through socialization and practice of product photography using smartphones. The activity was held on Tuesday, October 28, 2025, with stages including preparation of seaweed dodol products in two flavors (melon and pineapple), socialization of basic product photography techniques, and photography practice by KWT members. The results of the activity showed an increase in participants' understanding and skills in producing more visually appealing product photos.